Assessment the Role of Ubiquinone (Coenzyme Q10) against Spermatotoxic Effect of Busulfan in Male Rats (Indian Journal of Forensic Medicine & Toxicology, 2021)
Busulfan is a chemotherapy treatment for cancer patients, and in comparison with the coenzyme ubiquinoneis a coenzyme that works to enhance chemical reactions and protect the body from free radicals. It helps intreating cancer and protecting patients undergoing chemotherapy. This study was aimed to investigate therole of ubiquinone against the toxic effect of busulfan on sperm in adult white rats for a period of time, andthe experiment was carried out for eight weeks on 24 male adult rats were used, the study was conductedin periods (day 28 ). Distributed in four groups randomly and equally in each group of 6 male rats. Thecontrol group injected with distilled water intraperitoneally , second group were injected with busulfan(chemotherapy) only one dose of 10 mg / kg. while animals of third group injected with single dose ofbusulfan 10 mg / kg plus coenzyme ubiquinone COQ10) 10 mg / kg ) for 4 weeks, while animals in fourthgroup were injected with the coenzyme ubiquitin coenzyme (COQ10) 10 mg / kg for 4 weeks. At the endof experiment the blood was collected for measuring of blood parameters and hormones levels and spermanalysis has benn done
Keywords: CoQ10; Busulfan, Chemotherapy